First record of Lyophyllum shimeji mashrooms in Dazhou. (October 2019) - Xu, D; Sun, C Q; Li, B; Xu, J J; Zhao, H; Wang, Z D; Ma, J
Abstract: a new record of Lyophyllum shimeji was collected during field trip to masson pine at Dazhou (31.35° N, 107.72° E; 1100 m altitude) district in 16th of October 2017. It was identified using morphological and molecular techniques. Complete description was performed for the collected fresh fruiting bodies and isolated pure culture. Radial growth rate of culture was estimated on media1, media 2, media 3, media 4, media 5 and media 6 (0.196, 0.192, 0.122, 0.092, 0.200, 0.160 cm/day, respectively). Lyophyllum are very close in morphological characters; hence, the identification was confirmed by DNA sequence analysis of the ribosomal 5.8S rRNA gene including the flanking internal transcribed spacers (ITS). The results showed that it was Lyophyllum shimeji and this is the first record in other parts of China. The suitable culture medium component was potato 200g, MgSO4 -7H2 O 0.5g, glucose 20 g, KHM2 PO4 0.3 g, tryptone 0.5 g, VB1 20 mg, ager 20 g, ddH2 O 1000ml, PH5-6. These results could provide a new reference for its artificial domestication and cultivation studies.